2016
DOI: 10.3390/rs8090723
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Variations of Archaeological Marks at Neolithic Site of Lucera, Italy Using High-Resolution Multispectral Datasets

Abstract: Satellite images have been systematically explored by archaeologists to detect crop marks, which are considered as a proxy for the identification of buried archaeological remains. Even though several existing algorithms are frequently applied, such as histogram enhancements and vegetation indices, the detection of crop marks still remains a difficult task, while the final interpretation results can be very poor. This paper aims to present some of the current difficulties of "remote sensing archaeology" in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…From the VIs tested, variants of the Simple Ratio (SR, MSR, GRVI), NDVI (NDVI, GNDVI) and ARI2 produced the highest degree of separability between the two sampled regions. This supports results from other studies, which have found the SR to be one of the most effective band combinations for highlighting crop marks (Agapiou et al, , ; Bennett et al, ). When assessed in isolation, the red and green bands were more effective for detecting change across the sample region than the individual red‐edge and NIR bands.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…From the VIs tested, variants of the Simple Ratio (SR, MSR, GRVI), NDVI (NDVI, GNDVI) and ARI2 produced the highest degree of separability between the two sampled regions. This supports results from other studies, which have found the SR to be one of the most effective band combinations for highlighting crop marks (Agapiou et al, , ; Bennett et al, ). When assessed in isolation, the red and green bands were more effective for detecting change across the sample region than the individual red‐edge and NIR bands.…”
Section: Discussionsupporting
confidence: 90%
“…Note: Agapiou et al, , ; Agapiou, Hadjimitsis, et al, ; Bennett et al, ; Birth & McVey, ; Challis et al, ; Deering, ; Jordan, ; Pearson & Miller, ; Verhoeven & Doneus, . ρ GREEN , ρ RED , ρ RED‐EDGE , ρ NIR : reflectance across broad green, red, red‐edge and near infrared wavelength bands.…”
Section: Study Area and Data Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purposes of our investigations, the "Tavoliere delle Puglie", a plain in northern Apulia (Southern Italy), was selected as a test area due to its long human frequentation and, consequently, its high archaeological potential and variety of cultural heritage features, along with a huge amount of ancillary data and information also available in a GIS environment. In the past the area herein investigated has been widely studied also using very high resolution satellite data as QuickBird, World View [13], geophysical prospection [14,15], along with manned [16][17][18][19][20] and unmanned aerial archaeology prospection [21]. Archaeological recorders along with previous knowledge and information already available in GIS environment are herein adopted as ground truth [22][23][24][25][26][27] to assess the potentiality of Sentinel-2 data in known archaeological sites related to different periods and civilizations, from Neolithic era to Greek-Roman and Middle Ages [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%